Anticancer Activity of Buttermilk Against SW480 Colon Cancer Cells is Associated with Caspase-Independent Cell Death and Attenuation of Wnt, Akt, and ERK Signaling. (2nd October 2016) - Kuchta-Noctor, Anna M.; Murray, Brian A.; Stanton, Catherine; Devery, Rosaleen; Kelly, Phil M.
ABSTRACT: Buttermilk is a rich source of milk fat globule membrane (MFGM) fragments assembled from bioactive polar lipids and proteins that originate from bovine mammary epithelial cells. The objective of this study was to examine growth-modulatory effects of experimental buttermilks varying in sphingolipid and phospholipid composition on a colon cancer cell line of human origin. Buttermilks were prepared from washed and unwashed cream using gravity or centrifugation. Compositional analysis showed that sphingomyelin (SM) (10.4–29.5%) and lactosylceramide (LacCer) (1.2–44.3%) were the predominant sphingolipids detected. Experimental samples inhibited in vitro growth of SW480 colon cancer cells in a dose-dependent manner. Antiproliferative activity was selective toward cancer cells. A fraction enriched in LacCer (44.3%), obtained by microfiltration induced caspase-independent cell death as evident by phosphatidylserine externalization, increased percentage of degraded DNA, and loss of mitochondrial membrane potential in SW480 cells. This fraction downregulated growth-signaling pathways mediated by β-catenin, phosphorylated Akt (serine/threonine-specific protein kinase), ERK1/2 (extracellular signal–regulated kinase), and c- myc . This study is to our knowledge the first to screen buttermilk samples that vary in polar lipid composition for antiproliferative activity in vitro.